Extensive and every day risk in the Bolivian Chaco: Sources of crisis and disaster - Lilian R. Reyes Pando; Allan Lavell (Revue de Géographie Alpine)
Disaster risk comprises a continuum, ranging from primary-structural (pre-impact), through contingent (resulting from impact) to future or reconstructed risk (resulting from inadequate recovery or reconstruction practices). At the same time these categories are many times constructed on the basis of existing chronic risk. These different categories are employed to demonstrate how the 2009-2011 disasters associated with the drought and freezing that affected the Bolivian Chaco region evolved and were perpetuated in cyclical manner. Additionally, the article demonstrates how preconceived notions of causal factors and post impact needs analysis, associated with large scale, rapid onset hazards, belies an understanding of the needs in slow onset and lifestyle based extensive risk crises. It also reveals how any attempt to deal with the successive, apparently sequenced categories of risk, using independent mechanisms and institutional frameworks is doomed to failure due to the relations that exist between primary, contingent and future risk and the disaster risk management and development mechanisms required to reduce them.